Uniform Sb(2)S(3) optical coatings by chemical spray method - Eensalu, Jako S (Beilstein J Nanotechnol, 2019)
Antimony sulfide (Sb(2)S(3)), an environmentally benign material, has been prepared by various deposition methods for use as a solar absorber due to its direct band gap of ≈1.7 eV and high absorption coefficient in the visible light spectrum (1.8 × 10(5) cm(−1) at 450 nm). Rapid, scalable, economically viable and controllable in-air growth of continuous, uniform, polycrystalline Sb(2)S(3) absorber layers has not yet been accomplished. This could be achieved with chemical spray pyrolysis, a robust chemical method for deposition of thin films. We applied a two-stage process to produce continuous Sb(2)S(3) optical coatings with uniform thickness. First, amorphous Sb(2)S(3) layers, likely forming by 3D Volmer–Weber island growth through a molten phase reaction between SbCl(3) and SC(NH(2))(2), were deposited in air on a glass/ITO/TiO(2) substrate by ultrasonic spraying of methanolic Sb/S 1:3 molar ratio solution at 200–210 °C. Second, we produced polycrystalline uniform films of Sb(2)S(3) (E(g) 1.8 eV) with a post-deposition thermal treatment of amorphous Sb(2)S(3) layers in vacuum at 170 °C, <4 × 10(−6) Torr for 5 minutes. The effects of the deposition temperature, the precursor molar ratio and the thermal treatment temperature on the Sb(2)S(3) layers were investigated using Raman spectroscopy, X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy and UV–vis–NIR spectroscopy. We demonstrated that Sb(2)S(3) optical coatings with controllable structure, morphology and optical properties can be deposited by ultrasonic spray pyrolysis in air by tuning of the deposition temperature, the Sb/S precursor molar ratio in the spray solution, and the post-deposition treatment temperature.